Necessary risks : challenges privileged people need to face - Ott, Teri McDowell (Fortress Press, 2022)
In Necessary Risks, Teri McDowell Ott explores her wrestling, as a privileged white Christian woman, with ten risks and the underlying systems and structures that need to be changed. Such risks, she argues, transform individuals and communities, creating a path toward a more equitable and just world.